Effect of acquisition technique on radiation dose and image quality in multidetector row computed tomography coronary angiography with submillimeter collimation - Gerber, Thomas C; Stratmann, Brian P; Kuzo, Ronald S; Kantor, Birgit; Morin, Richard L (Investigative radiology, 2005)
We sought to examine effects of tube voltage and current on radiation dose and image quality for minimally invasive coronary angiography with a 16-slice multidetector row computed tomography (MDCT) scanner. We scanned the phantom used in the American College of Radiology Computed Tomography Accreditation Program at tube voltages of 80 and 120 kVp at 550, 650, and 750 mAseff, with and without a reduction in radiation dose by electrocardiographically (ECG) controlled tube current modulation (ECG pulsing). Without ECG pulsing, the effective dose was 3 to 13 mSv. On average, a 50% increase in tube voltage led to increased radiation dose (215%), contrast-to-noise ratio (150%), and decreased image noise (-48%). On average, a 17% increase in mAseff led to increased radiation dose (17%) and contrast-to-noise ratio (4%) and decreased image noise (-9%). Dose reduction by ECG pulsing (simulated heart rate, 70 beats per minute) was 28%. With ECG pulsing, noise in images reconstructed during ventricular systole was double that in images reconstructed during ventricular diastole. These quantitative findings about the relationships among scan acquisition parameters, radiation dose, and image quality have practical implications for using ECG pulsing to reduce radiation doses in MDCT coronary angiography.